Seed storage in polyethylene bags of a recalcitrant species (Quercus ilex): analysis of some bio-energetic and oxidative parameters - Pasquini, Sergio; Mizzau, Michela; Petrussa, Elisa; Braidot, Enrico; Patui, Sonia; Gorian, Fabio; Lambardi, Maurizio; Vianello, Angelo (Acta Physiologiae Plantarum, 2012)
Some technological and physiological aspects were analysed during seed storage of holm oak (Quercus ilex L.), a typical Mediterranean recalcitrant species. Considering the mild dormancy and desiccation sensitivity of these seeds, the inﬂuence of the storage environment on viability was examined. Acorns were maintained at low temperature and at high moisture content either inside thin polyethylene bags or mixed with peat in a bin. Storage in polyethylene bags, if compared with peat treatment, maintained optimal seed quality parameters. The effects of the two treatments on some physiological parameters were analysed during 1-year seed storage. Acorns stored in a bin with peat started to germinate early and exhibited a more rapid seed deterioration caused by metabolism-linked oxidative damage. The latter phenomenon was linked to a higher respiration and H2O2 level, induction of catalase activity, as well as lowered glutathione pool and ATP content. In addition, a more oxidized redox poise was observed. On the contrary, the plastic ﬁlm of polyethylene, limiting gaseous exchanges, maintained acorn metabolic activity at low levels and allowed the accumulation of ethylene inside the storage atmosphere. These factors, inducing a dormant-like state, could have played a crucial role in prolonging seed storage.
Keywords: antioxidant; ethylene; Holm oak; storage

Comportement physiologique des glands de chêne liège (Quercus suber L.) durant leur conservation et variabilité inter-individus producteurs - Merouani, Hachemi; Branco, Carmen; Almeida, Maria Helena; Pereira, João S. (Ann. For. Sci., 2001)
The mature acorns were harvested on twelve selected trees from a cork oak population in Southern Portugal (Herdade da Palma). After drying, the seed lots were stored on three types bags (polyethylene with 30 mm and 50 mm thick and plastic mesh), for six months at 0 oC. At the time of natural dissemination, the acorns from the majority of the trees from the same population were under the same state of morphological and physiological maturity. The moisture content was about 44-47% and a germination rate above 92% . At this time, the germination was very slow because of the existent embryonic dormancy that seems to be dependent on the individual trees. During the storage, germination rate is improved. This might be explained by the breaking dormancy during storage. The mean germination time was on an average 10 days for fresh seeds and decreased to about 4 days after 6 months storage. A relationship between viability and seed moisture content was observed. The Mean Germination Time of dried seed and stored seed for 4 months in plastic mesh bag increased to about 13 days. The germination capacity was strongly decreased when the seed moisture content was below 30%
Keywords: electrolyte leakage; germination; Moisture content; Quercus suber; seed; storage

Comportement physiologique des glands de chêne liège (Quercus suber L.) durant leur conservation et variabilité inter-individus producteurs - Merouani, Hachemi; Branco, Carmen; Almeida, Maria Helena; Pereira, João S (Ann. For. Sci., 2001)
The mature acorns were harvested on twelve selected trees from a cork oak population in Southern Portugal (Herdade da Palma). After drying, the seed lots were stored on three types bags (polyethylene with 30 mm and 50 mm thick and plastic mesh), for six months at 0 oC. At the time of natural dissemination, the acorns from the majority of the trees from the same population were under the same state of morphological and physiological maturity. The moisture content was about 44-47% and a germination rate above 92% . At this time, the germination was very slow because of the existent embryonic dormancy that seems to be dependent on the individual trees. During the storage, germination rate is improved. This might be explained by the breaking dormancy during storage. The mean germination time was on an average 10 days for fresh seeds and decreased to about 4 days after 6 months storage. A relationship between viability and seed moisture content was observed. The Mean Germination Time of dried seed and stored seed for 4 months in plastic mesh bag increased to about 13 days. The germination capacity was strongly decreased when the seed moisture content was below 30%
Keywords: electrolyte leakage; germination; Moisture content; Quercus suber; seed; storage